Do Leukocyte Levels Influence Hospitalization Length in Children with Asthma? A Retrospective Cohort Study - Puspita, Gina; Zain Nuha Silmy Hidayati (HM Publisher, 2025)
Asthma is a prevalent chronic respiratory disease in children, characterized by airway inflammation and obstruction. Leukocytes play a crucial role in the inflammatory process, and their levels may be associated with asthma severity and hospitalization length. This study aimed to investigate the relationship between leukocyte counts and the length of hospital stay in children with asthma. A retrospective cohort study was conducted using medical records of pediatric asthma patients admitted to PKU Muhammadiyah Gamping Hospital between 2018 and 2023. Data on demographics, leukocyte counts, and length of hospitalization were collected. Statistical analysis was performed using SPSS 29.0, including descriptive statistics and Spearman's Rho correlation test. A total of 130 patients were included. The majority were male (61.53%) and aged 2-5 years (85.38%). Leukocytosis was observed in 63.07% of patients, while 6.92% had leukopenia. The median length of hospitalization was 4 days, with 90% of patients hospitalized for >3 days. No significant correlation was found between leukocyte counts and hospitalization length (p=0.144, r=-0.129). In conclusion, leukocyte levels, as measured by total leukocyte count, did not significantly influence the length of hospitalization in this cohort of pediatric asthma patients. Further research considering specific leukocyte subtypes and other factors may provide a more comprehensive understanding of the relationship between inflammation and hospitalization duration in this population.